Cost Consequences of a Port-Related Supply Chain Disruption - Loh, Hui Shan (2016)
Port functionality is a significant and important aspect of cargo transportation. Previous studies have identified a list of port-related supply chain disruption threats and developed a management model that seeks to address these threats. This paper adds value to these related studies by comparing four consequences of an example of these threats: (1) avoidance of disruption, (2) mitigation of disruption, (3) deviation of transportation plan and (4) delays and deviation of transportation plan. The impact of these consequences is simulated in a case study using data from a chemical manufacturer based in Singapore. This paper quantitatively measures the impact of a port-related threat on supply chains and thus highlights the importance of port-related supply chain disruption management.